SOME FACTORS AFFECTING PROPERTIES AND DISSOLUTION BEHAVIOR OF TABLETTED FUROSEMIDE MICROSPHERES - (:unkn) unknown (GOVI-VERLAG GMBH, 1992)
The microspheres are prepared by the solvent-evaporation method [5] after a technology worked out in our laboratory. The polymer (3 g) was dissolved in CH3COCH3 in a solvent: polymer ratio of 9:1 (v/w) by stirring (500 r.p.m., MLW25MR Mixer, Berlin); magnesium stearate (0.1 g) and 1 (1 g) are added during the process of stirring. It continues at the same rate for another 15 min, when it was speeded up to 2800 r.p.m. and a mixture of liquid paraffin (270 ml) and n-C6H14 (30 ml) was added. After the CH3COCH3 evaporation (about 50 min), the microspheres are liberated from the mineral oil by filtration in vacuum first and then by a fivefold wash in 50 ml n-C6H14 each. The microspheres are dried in vacuum at room temperature for 24 h. The models of the prepared microspheres are presented in the Table.
Keywords: MICROCAPSULES; RELEASE